Thought Processes in Producing Casual Speech - Riza Amelia (ELITE Association Indonesia, 2023)
ABSTRACT This study aims to investigate the thought processes involve in the production of casual speech. Casual speech production is characterized by the existence of low power and distance among language users; therefore, the speakers find it cognitively easier to produce. The design of the research was qualitative. Ten EFL pre-service teachers were recruited as the research participants. The participants were requested to act out some scenarios of roleplay in the format of casual speech, namely, (1) self-introduction, (2) talking about hobbies, (3) talking about memorable memories, (4) commenting the viral issues on social media, (5) commenting about hopes for the next president of Indonesia. The participants were told to reveal all thought processes that they could observe in their mental during each speech production of the scenarios immediately. The participants’ verbal reports were recorded via writing. The results of the interview were transcribed and analyzed to find the patterns of thought processes in producing casual speech for each scenario. The findings showed that self-introduction and telling hobbies happened relatively fast as all the speakers did not involve in much thinking preparation in term of conceptual, grammatical and phonological speech planning. However, for other speech situations, the difficulty were inline with the individuals’ language Keywords: Second language production; thought processes; casual speech.